2019
DOI: 10.1007/s11103-019-00889-9
|View full text |Cite|
|
Sign up to set email alerts
|

Wheat wounding-responsive HD-Zip IV transcription factor GL7 is predominantly expressed in grain and activates genes encoding defensins

Abstract: Wheat wounding-responsive HD-Zip IV transcription factor GL7 is predominantly expressed in grain and activates genes encoding defensins

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 89 publications
0
11
0
Order By: Relevance
“…These genes are generally expressed in the outer layer or epidermis [156,157], the same as the HD-ZIP IV subfamily genes. The durum wheat TdGL7 gene under wounding stress elevated significantly in the grain tissue, similarly to the defensins genes [158]. This provides potential grounds for the biotechnological manipulation of the TdGL7 gene in wheat to protect the grain from chewing insects or fungi [158].…”
Section: Hd-zip Iv: Role In Coping Biotic Stressmentioning
confidence: 94%
See 2 more Smart Citations
“…These genes are generally expressed in the outer layer or epidermis [156,157], the same as the HD-ZIP IV subfamily genes. The durum wheat TdGL7 gene under wounding stress elevated significantly in the grain tissue, similarly to the defensins genes [158]. This provides potential grounds for the biotechnological manipulation of the TdGL7 gene in wheat to protect the grain from chewing insects or fungi [158].…”
Section: Hd-zip Iv: Role In Coping Biotic Stressmentioning
confidence: 94%
“…sue, similarly to the defensins genes [158]. This provides potential grounds for the biotechnological manipulation of the TdGL7 gene in wheat to protect the grain from chewing insects or fungi [158].…”
Section: Solanum Tuberosummentioning
confidence: 99%
See 1 more Smart Citation
“…The isolation of the first HD-containing gene, maize KNOTTED1 marked the discovery of several HD-ZIP TFs which were identified and characterized in model and crop plants through genome-wide analyses [ 141 , 142 , 143 , 144 , 145 , 146 ]. Further studies showed that HD-Zip TFs are actively involved in transcriptional regulation of abiotic stress responses, light, and hormonal (ABA, auxin, and ethylene) signal transduction, and plant growth and development [ 119 , 147 , 148 , 149 , 150 , 151 , 152 , 153 , 154 , 155 , 156 ]. Various members of subfamilies were identified with roles in developmental networks [ 6 , 152 , 155 ].…”
Section: Molecular Structure and Regulation Of Transcription Factors During Drought And Associated Stressesmentioning
confidence: 99%
“…HD components of HD-Zip TFs are around 60 residues in length and consist of three α-helices ( Figure 4 C,D) connected by a loop and a turn [ 119 , 137 , 148 , 153 ]. The third α-helix, called the recognition α-helix (arrows in Figure 4 C,D), is the most conserved across HD proteins and is responsible for high-affinity binding between HD-Zip TF and the major groove of the target DNA, while the disordered NH 2 -terminal component, located upstream of the first α-helix, interacts with the DNA minor groove [ 146 ].…”
Section: Molecular Structure and Regulation Of Transcription Factors During Drought And Associated Stressesmentioning
confidence: 99%